Secondary post-oncologic vulvar reconstruction – a simplified algorithm - Caretto, Anna Amelia; Servillo, Maria; Tagliaferri, Luca; Lancellotta, Valentina; Fragomeni, Simona Maria; Garganese, Giorgia; Scambia, Giovanni; Gentileschi, Stefano (Frontiers in Oncology, 2023)
INTRODUCTION Surgical treatment is the gold standard of care for vulvar cancer and is burdened by a high risk of wound complications due to the poor healing typical of the female genital area. Moreover, this malignancy has a high risk of local relapse even after wide excision. For these reasons, secondary reconstruction of the vulvoperineal area is a relevant challenging scenario for gynecologist and plastic surgeon. The presence of tissue already operated and undermined, scars, incisions, possibility of previous radiation therapy, contamination of urinary and fecal pathogens in the dehiscent wound or ulcerated tumor and the unavailability of some flaps employed during the primary procedure are typical complexities of this surgery. Due to the rarity of this tumor, a rational approach to secondary reconstruction has never been proposed in the Literature. METHODS In this observational retrospective study, we reviewed the clinical data of patients affected by vulvar cancer and undergone to secondary reconstruction of the vulvoperineal area in our hospital between 2013 and 2022. Oncological, reconstructive, demographic data and complications were recorded. The primary outcome measure was the incidence of wound complications. The secondary outcome measure was the indication to the different flaps, according to the defect, to establish an algorithm for decision-making. RESULTS Sixty-six patients were included, mean age was 71.3± 9.4 years and mean BMI 25.1±4.9. The mean size of the defect repaired by secondary vulvar reconstruction was 178cm2 + 163cm2. Vertical Rectus Abdominis Myocutaneous (VRAM), Anterolateral Thigh (ALT), fasciocutaneous V-Y (VY) and Deep Inferior Epigastric Perforator (DIEP) were the flaps more frequently employed. We observed 5 cases of wound breakdown, 1 case of marginal necrosis of an ALT flap, 3 cases of wound infection. The algorithm we developed considered the geometry and size of the defect and the flaps still available after previous surgery. DISCUSSION A systematic approach to secondary vulvar reconstruction can provide good surgical results with a low rate of complication. The geometry of the defect and the use of both traditional and perforator flaps should guide the choice of the reconstructive technique.